Heterologous SARS‐CoV‐2 IgA neutralising antibody responses in convalescent plasma. Issue 10 (23rd October 2022) - Davis, Samantha K; Selva, Kevin John; Lopez, Ester; Haycroft, Ebene R; Lee, Wen Shi; Wheatley, Adam K; Juno, Jennifer A; Adair, Amy; Pymm, Phillip; Redmond, Samuel J; Gherardin, Nicholas A; Godfrey, Dale I; et al.
Abstract: Objectives: Following infection with SARS‐CoV‐2, virus‐specific antibodies are generated, which can both neutralise virions and clear infection via Fc effector functions. The importance of IgG antibodies for protection and control of SARS‐CoV‐2 has been extensively reported. By comparison, other antibody isotypes including IgA have been poorly characterised. Methods: Here, we characterised plasma IgA from 41 early convalescent COVID‐19 subjects for neutralisation and Fc effector functions. Results: Convalescent plasma IgA from > 60% of the cohort had the capacity to inhibit the interaction between wild‐type RBD and ACE2. Furthermore, a third of the cohort induced stronger IgA‐mediated ACE2 inhibition than matched IgG when tested at equivalent concentrations. Plasma IgA and IgG from this cohort broadly recognised similar RBD epitopes and had similar capacities to inhibit ACE2 from binding to 22 of the 23 prevalent RBD mutations assessed. However, plasma IgA was largely incapable of mediating antibody‐dependent phagocytosis in comparison with plasma IgG. Conclusion: Overall, convalescent plasma IgA contributed to the neutralising antibody response of wild‐type SARS‐CoV‐2 RBD and various RBD mutations. However, this response displayed large heterogeneity and was less potent than IgG. Abstract : Following infection with SARS‐CoV‐2, virus‐specific antibodies are generated, which can both neutralise virions and clear infection via Fc effector functions. Here, we demonstrate that convalescent plasma IgA was largely incapable of mediating antibody‐dependent phagocytosis in comparison with plasma IgG. However, IgA from > 60% of the cohort had the capacity to neutralise SARS‐CoV2 wild‐type and numerous RBD variants, although this response was heterogeneous and less potent than IgG.